Promoting transparency on agricultural policies at the WTO: Lessons from Latin America and the Caribbean - Vargas, Adriana García (Instituto Interamericano de Cooperación para la Agricultura, 2021)
Transparency is present across all three pillars of the WTO Agriculture negotiations, with many technical submissions and proposals by WTO members that either address transparency exclusively, or include related elements within the areas they cover91. The suggestions range from improving the implementation of the notification requirements established by the Agreement on Agriculture (AoA), to creating new notification requirements or modifying the existing ones.